Na esquina do rio amazonas: requalificação da praça Santa Inês escrita pela práxis cultural - (:unkn) unknown (UNIFAP – Universidade Federal do Amapá)
As a result of concerns about the public space, this research focuses on the understanding of what is the public urban space, especially which concerns Praça do Santa Inês, located in the city of Macapá, Amapá. The investigation enters into dialogues about the negligence of updating public policies that support the construction and insertion of this public space in the city. In addition, it investigates how cultural praxis and participatory planning acts as tools for confronting socio-spatial segregation and socio-urban problems. In view of this, the objective of this monograph is to understand how participatory urban planning and its methodologies can contribute to the development of an urban redevelopment project for Praça do Santa Inês and its surroundings, on the banks of the Amazon River, in the city of Macapá, transposing this into an urban-architectural project. About the methodological procedures to achieve this goal, the research is, a priori, a bibliographic survey and participatory research for the apprehension of the object of study, also including participatory methodologies to answer the theoretical questions of the investigation, clarifying the public urban space, its needs and configurations in the contemporaneity of the place and the city, thus paving the way for the proposed urban redevelopment of Praça do Santa Inês. The result of the path studied is the urban redevelopment project translated into the “Amazon River Corner Complex”, a project that encompasses the square, a gastronomic block and a pier that allows for greater connection with the bathing river in front of Macapá city.
Keywords: Espaço urbano público; Planejamento urbano participativo; Praça do Santa Inês - Projeto arquitetônico; Requalificação urbana - Projeto; CNPQ::CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO